(untitled) (Academia Journal of Medicine, 2019)
Background: Snakebite envenoming is a potentially life-threatening disease that typically results from the injection of venom following the bite of a venomous snake. Sometimes envenoming can also be caused by venom being sprayed into a person’s eyes by certain species of snakes that have the ability to spit venom as a defense measure. Not all snakebites are venomous. Some snakes are non-venomous and venomous snakes do not always inject venom during a bite. Subjects and Methods: Patients were examined for complications of snake bite. Haemotoxicity was assessed based on features like bleeding from the bite site, gums, epistaxis, haemoptysis, haematemesis, rectal bleeding or malaena, haematuria, vaginal bleeding, bleeding into the mucosae, skin (petechiae, purpura, discoid haemorrhages, ecchymoses. Neurotoxicity by drowsiness, paraesthesiae, abnormalities of taste and smell, ptosis, external ophthalmoplegia, paralysis of facial muscles and other muscles innervated by the cranial nerves, respiratory and generalized flaccid paralysis. Results: Majority of the patients were farmers with 44% followed by housewives (26%). Lower limbs were the most common site of bite in our study group comprising of74% of the patients. Conclusion: Most common manifestation of envenomation is local envenomation comprising of 66%.